The Force Awakens: The Role of Social Media Marketing on SMEs Context in Makassar (A Case Study Approach) - Tafsir, Muh.; Mustafa, Muh. Yushar (Entrepreneurship, Management, and Business Research Journal, 2025)
This research examines the role of social media marketing in small and medium enterprises (SMEs) in Makassar, Indonesia, employing a case study approach to provide an in-depth understanding of its impact. As the digital landscape evolves, SMEs are increasingly turning to social media platforms to enhance their marketing strategies, engage with customers, and promote their products and services. This study analyses various SMEs across different sectors in Makassar to identify the benefits and challenges associated with social media marketing. The findings reveal that social media marketing significantly contributes to increased brand awareness, customer engagement, and sales growth for SMEs. Businesses that effectively utilize platforms like Facebook, Instagram, and Twitter report improved customer relationships and greater market reach. However, challenges such as limited digital literacy, resource constraints, and heightened competition hinder the effective implementation of social media strategies. This research highlights the need for targeted training programs to enhance digital skills among SME owners and employees, enabling them to leverage social media marketing more effectively. By providing insights into best practices and strategies, this study aims to assist SMEs in Makassar in optimizing their social media marketing efforts, ultimately contributing to their growth and sustainability in a competitive marketplace. Studi ini menganalisis berbagai UKM di berbagai sektor di Makassar untuk mengidentifikasi manfaat dan tantangan yang terkait dengan pemasaran media sosial. Temuan menunjukkan bahwa pemasaran media sosial secara signifikan berkontribusi pada peningkatan kesadaran merek, keterlibatan pelanggan, dan pertumbuhan penjualan untuk UKM. Bisnis yang secara efektif memanfaatkan platform seperti Facebook, Instagram, dan Twitter melaporkan peningkatan hubungan dengan pelanggan dan jangkauan pasar yang lebih luas. Namun, tantangan seperti literasi digital yang terbatas, keterbatasan sumber daya, dan persaingan yang semakin ketat menghambat implementasi strategi media sosial yang efektif. Penelitian ini menyoroti perlunya program pelatihan yang ditargetkan untuk meningkatkan keterampilan digital di antara pemilik dan karyawan UKM, sehingga mereka dapat memanfaatkan pemasaran media sosial secara lebih efektif. Dengan memberikan wawasan tentang praktik dan strategi terbaik, penelitian ini bertujuan untuk membantu UKM di Makassar dalam mengoptimalkan upaya pemasaran media sosial mereka, yang pada akhirnya berkontribusi pada pertumbuhan dan keberlanjutan mereka di pasar yang kompetitif.